(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The reduction of *yo to (y)e, already known from the ancient Ligurian onomastics (§ 1), is identified as one of the specifically Celtic isoglosses of the dialect spoken in that region, therefore to be called Celto-Ligurian (§ 2). The sound-change accounts for the religious loan-word dekantem ‘the tenth’ in the Narbonensis, which, due to the cultural contacts with Ligury (§ 3), developed from a neuter substantive *dekÚm9t-yo-m (§ 4), while the more archaic ordinal number *dekÚm9to- is still preserved as deganto- (CIL II 5762) )in Spain (§ 5), prior to its modernization in CIb. dekametam (§ 6). Apart from plant names either glossed as Celtic or found in the proximity of Ligury (§ 7), the monophthongization of *yo is recognized in the ending -(n/s)ken of thirteen coin legends from the Catalonian coast (§§ 8-9), originating in the IE and Celtic genitive plural *-nk/sk-yom of the respective inhabitant names (neronken ‘of the Neronikyoi or Manly people’, (b)olsken < *Volskyom, arsesken ‘of the Arseskii, i.e.of the inhabitants of Arse’ etc.) and thus increasing the already rich Palaeohispanic form-variation for this case (§ 10). Finally, the monophthongization seems to have affected some Aquitanian theonyms, Celtic (such as Anderio(n), Andotios and Artaios) as well as Classical (§11).